2017
DOI: 10.1016/j.ram.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Azotobacter chroococcum as a potentially useful bacterial biofertilizer for cotton ( Gossypium hirsutum ): Effect in reducing N fertilization

Abstract: The aim of this research was to evaluate whether the application of two plant growth-promoting (rhizo)bacteria might reduce nitrogen fertilization doses in cotton. We used strains Azotobacter chroococcum AC1 and AC10 for their proven ability to promote seed germination and cotton growth. These microorganisms were characterized by their plant growth-promoting activities. Then, we conducted a glasshouse study to evaluate the plant growth promoting ability of these strains with reduced doses of urea fertilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 27 publications
1
49
1
3
Order By: Relevance
“…Usually, hydroxamates are more commonly found in neutral to acid environments while catecholates are more commonly found in neutral to alkaline environments (Saha et al, 2013). Several bacterial genera were described to produce siderophores, such as Azotobacter (Baars et al, 2016;McRose et al, 2017;Romero-Perdomo et al, 2017), Azospirillum (Banik et al, 2016), Bacillus (Kesaulya et al, 2018;Pourbabaee et al, 2018), Dickeya (Sandy and Butler, 2011), Klebsiella (Bailey et al, 2018;Zhang et al, 2017), Nocardia (Hoshino et al, 2011), Pantoea (Burbank et al, 2015;Soutar and Stavrinides, 2018), Paenibacillus (Liu et al, 2017), Pseudomonas (Baune et al, 2017;Deori et al, 2018;Pourbabaee et al, 2018), Serratia (Coulthurst, 2014) and Streptomyces (Gáll et al, 2016;Goudjal et al, 2016;Schütze et al, 2014).…”
Section: Siderophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, hydroxamates are more commonly found in neutral to acid environments while catecholates are more commonly found in neutral to alkaline environments (Saha et al, 2013). Several bacterial genera were described to produce siderophores, such as Azotobacter (Baars et al, 2016;McRose et al, 2017;Romero-Perdomo et al, 2017), Azospirillum (Banik et al, 2016), Bacillus (Kesaulya et al, 2018;Pourbabaee et al, 2018), Dickeya (Sandy and Butler, 2011), Klebsiella (Bailey et al, 2018;Zhang et al, 2017), Nocardia (Hoshino et al, 2011), Pantoea (Burbank et al, 2015;Soutar and Stavrinides, 2018), Paenibacillus (Liu et al, 2017), Pseudomonas (Baune et al, 2017;Deori et al, 2018;Pourbabaee et al, 2018), Serratia (Coulthurst, 2014) and Streptomyces (Gáll et al, 2016;Goudjal et al, 2016;Schütze et al, 2014).…”
Section: Siderophoresmentioning
confidence: 99%
“…Due to their plant-growth promoting traits, Azotobacter spp. have been applied into plants to evaluate their capabilities to improve crop yields; examples are: cotton (Chauhan et al, 2012;Romero-Perdomo et al, 2017), sesame (Dubey et al, 2012), maize (Shirinbayan et al, 2019), wheat (Mahato and Kafle, 2018), rice (Sahoo et al, 2013), tomato (Chauhan et al, 2012), or maize (Shirinbayan et al, 2019). Growth improvement was measured through the increase to disease resistance (Chauhan et al, 2012;Dubey et al, 2012), plant biomass (Mahato and Kafle, 2018;Romero-Perdomo et al, 2017;Shirinbayan et al, 2019), nitrogen and Fe concentration (Shirinbayan et al, 2019), grain yield (Dubey et al, 2012;Mahato and Kafle, 2018) and drought resistance (Shirinbayan et al, 2019).…”
Section: Promising Bacterial Genera For Agricultural Practicesmentioning
confidence: 99%
“…Thus PGPR and their interactions with plants have great application prospects in ecological agriculture and sustainable agriculture. Coinoculation of cotton with Azotobacter chroococcum strains can positively influence plant growth and reduce nitrogen fertilization doses by 50% [20]. Korir et al [21] conducted experiments using a low-phosphorous soil under greenhouse conditions to examine the effect of PGPR on the nodulation and growth of common bean.…”
mentioning
confidence: 99%
“…PGPB can promote plant growth and yield under both normal and stress conditions (Viscardi et al, 2016). Azotobacter chroococcum is an N-fixing PGPB that has been shown to promote plant growth under a variety of soil types and climatic conditions, and the bacterium A. chroococcum is able to ameliorate negative effects of abiotic stresses (Romero-Perdomo et al, 2017). Viscardi et al (2016) reported that some strains of A. chroococcum could alleviate drought stress effects in tomato plants.…”
mentioning
confidence: 99%